The Role of Negative Pressure Wound Therapy in Burn Wound Healing - Sitti Khusnul Khatima; Reeny Purnamasari; Nurul Rumila Roem; Agung Kurniawan; Dian Amelia Abdi (Jurnal EduHealth, 2026)
Burn injuries represent a major health concern with high morbidity and a substantial risk of complications, including infection, delayed wound healing, and skin graft failure. Negative Pressure Wound Therapy (NPWT) has emerged as an increasingly utilized therapeutic modality in burn management, working through mechanisms such as edema reduction, enhanced tissue perfusion, stimulation of granulation tissue formation, and effective exudate control. This study employed a Systematic Literature Review design conducted in accordance with the PRISMA guidelines. The findings indicate that NPWT provides significant positive effects on clinical outcomes, including accelerated wound healing, reduced infection rates, improved graft take following split-thickness skin graft procedures, and shorter hospital length of stay. Furthermore, NPWT has been shown to be effective in emergency department and intensive care unit settings as a bridging intervention prior to definitive surgical management in patients with severe burn injuries. Nevertheless, variability in study designs, negative pressure parameters, and application techniques remains a challenge for the standardization of therapeutic protocols. Therefore, further well-designed randomized controlled trials are required to optimize clinical guidelines and establish appropriate patient selection criteria. Overall, NPWT represents an effective and recommended therapeutic option in modern burn wound management.